Medium-temperature curing epoxy resin glue solution, preparation method thereof and application of medium-temperature curing epoxy resin glue solution in fiber reinforced plastic pressure-bearing pipeline
By preparing a medium-temperature curing epoxy resin solution and using specific components to form an interpenetrating cross-linked structure, the problem of high temperature and high energy consumption in fiber-reinforced plastic pressure pipes was solved, achieving low-energy-consumption, high-efficiency production and excellent mechanical properties.
Patent Information
- Application Number
- CN202411393027.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-07
AI Technical Summary
Existing fiber-reinforced plastic pressure pipes have high curing temperatures, long curing times, and high energy consumption, resulting in low production efficiency.
A medium-temperature curing epoxy resin solution preparation method is adopted, which involves adding components such as wetting agents, amine compounds, acid anhydrides, and quaternary ammonium salt compounds to form a cross-linked structure of polyester and polyether interpenetrating or semi-interpenetrating, thereby reducing the curing temperature and time.
The curing temperature was reduced by 20-45℃, the curing time was shortened by 1-5 hours, energy consumption was significantly reduced, production efficiency was improved, the alkali corrosion resistance and interfacial bonding strength of fiber-reinforced plastic pressure pipes were enhanced, and good mechanical properties were maintained.
Smart Images

Figure CN119264605A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of epoxy resins, and in particular relates to a medium-temperature curing epoxy resin adhesive, a preparation method thereof, and an application of the epoxy resin adhesive in a fiber-reinforced plastic pressure-bearing pipeline. Background Art
[0002] At present, fiber reinforced plastic pressure pipes generally use thermosetting resins, including epoxy resins, unsaturated resins, phenolic resins and vinyl resins. For pressure pipes with high requirements for mechanical properties, such as seawater desalination membrane shells, ultra-high pressure membrane shells and energy recovery membrane shells, high requirements are placed on the stiffness, interlaminar shear strength and compression strength of fiber reinforced plastics. Epoxy systems are generally selected, which can still maintain good mechanical properties under conditions of long-term illumination and high temperature, but their curing temperature is generally higher than 160°C, and the curing time is generally several hours to more than ten hours, with high energy consumption and low efficiency.
[0003] Since its introduction in 1938, epoxy resin has been widely used in aerospace, defense, electronics, machinery, construction, light industry and other fields due to its advantages such as high bonding strength, low shrinkage, good chemical stability, excellent electrical insulation, high mechanical strength and good processing performance. It is one of the important fine polymer materials in the world. Bisphenol A epoxy resin is the most widely used among epoxy resins because of its convenient source of synthetic raw materials, low cost, and the performance of the cured product can meet the diverse application requirements.
[0004] Bisphenol A epoxy resin can form cured products with different properties with a variety of different types of curing agents, catalysts, and additives. It has excellent physical and mechanical strength, chemical resistance, low shrinkage and other characteristics and is widely used in various modern fields. However, in the preparation of fiber-reinforced plastic pressure pipes, there are still problems such as high curing temperature, long curing time, high energy consumption, and low efficiency. On the basis of maintaining the mechanical properties, heat resistance and corrosion resistance of fiber-reinforced plastic pressure pipes, lowering the curing temperature, reducing the curing time, and reducing energy consumption will have outstanding economic and social benefits in saving costs and improving production efficiency. Summary of the invention
[0005] The purpose of the present invention is to solve the problems of high curing temperature, long curing time, high energy consumption and low efficiency when preparing fiber reinforced plastic pressure pipes. The present invention provides a medium-temperature curing epoxy resin glue and a preparation method thereof and its application in fiber reinforced plastic pressure pipes.
[0006] The technical solution of the present invention is as follows:
[0007] One of the purposes of the present invention is to provide a method for preparing a medium temperature curing epoxy resin glue solution, the method comprising:
[0008] S1: adding a wetting agent and an amine compound to a bisphenol A epoxy resin, stirring uniformly, and obtaining a mixture;
[0009] S2: adding a toughening agent and a quaternary ammonium salt compound to the acid anhydride, stirring evenly to obtain a mixture;
[0010] S3: Pour the S1 mixture into the S2 mixture and stir evenly;
[0011] S4: adding an anti-aging agent, stirring evenly, adding a thickener, stirring evenly, and obtaining epoxy resin glue after defoaming treatment.
[0012] It is further defined that the mass ratio of bisphenol A epoxy resin, acid anhydride, quaternary ammonium salt compound and amine compound is 90-110:60-80:1-3.5:0.3-2, the wetting agent is 0-3% of the mass of the epoxy resin, the toughening agent is 0-10% of the mass of the epoxy resin, the anti-aging agent is 0-2% of the mass of the epoxy resin, and the thickener is 0-5% of the mass of the epoxy resin.
[0013] It is further defined that the acid anhydride is methyltetrahydrophthalic anhydride, endomethanetetrahydrophthalic anhydride or methylhexahydrophthalic anhydride, the wetting agent is alkyl glycidyl ether polymer or N-(hydroxyalkyl)amine condensation polymer, the toughening agent is polypropylene glycol diglycidyl ether, fatty acid polyglycidyl ether, carboxyl liquid nitrile rubber or polyvinyl butyral, the antioxidant is a benzotriazole mixture, phenylformamidine compounds, fluoroboric acrylate or phenoxy mercuric alcohol, the thickener is white carbon black, the quaternary ammonium salt compound is dimethyldiallyl ammonium chloride (DADMAC), acryloyloxyethyltrimethylammonium chloride (DAC), methacryloyloxyethyltrimethylammonium chloride (DMC) or methacrylamidopropyltrimethylammonium chloride (MAPTAC), and the amine compound is triethanolamine, tris(2-hydroxypropyl)amine, tris(2-hydroxyethyl)methylamine or tris(2-hydroxyethyl)aminopropylamine.
[0014] It is further defined that the stirring time in S1, S2, S3 and S4 is 2-5 min, and the stirring speed is 50-500 r / min.
[0015] A second object of the present invention is to provide a medium-temperature curing epoxy resin adhesive prepared by the above preparation method.
[0016] The third object of the present invention is to provide an application of the above-mentioned medium-temperature curing epoxy resin adhesive in fiber-reinforced plastic pressure-bearing pipes.
[0017] A fourth object of the present invention is to provide a fiber reinforced plastic pressure pipe, which is prepared from the above-mentioned epoxy resin glue and fiber filaments.
[0018] A fifth object of the present invention is to provide a method for preparing the above-mentioned fiber reinforced plastic pressure pipe, wherein:
[0019] The fiber filaments are immersed in the above-mentioned medium-temperature curing epoxy resin adhesive, and then processed and prepared through a pipe mold thermosetting process.
[0020] It is further defined that the curing time of the thermosetting process is divided into two stages, the first stage temperature is 70-80°C, the constant temperature time is 2-3h, and the second stage temperature is 110-130°C, the constant temperature time is 4-6h.
[0021] A sixth object of the present invention is to provide an application of the above-mentioned fiber reinforced plastic pressure pipe in drainage.
[0022] Compared with the prior art, the advantages of the present invention are: compared with amine curing agents, the advantages of anhydride curing agents are low volatility, low toxicity, low irritation to the skin, long service life, easy operation, and a large proportion of addition can well reduce the viscosity after mixing with epoxy resin; compared with the combination of ordinary anhydride curing agents and tertiary amine accelerators, the curing reaction temperature is reduced and the alkali resistance is improved. The specific advantages are as follows:
[0023] (1) During the curing process, the maximum curing temperature of the fiber-reinforced plastic pressure-bearing pipe prepared by the medium-temperature curing epoxy resin adhesive of the present application is reduced by (20-45)°C and the curing time is shortened by (1-5) hours according to the thickness of the fiber-reinforced plastic pressure-bearing pipe, thereby greatly reducing energy consumption, shortening the production cycle, and improving production efficiency, which has significant social and economic benefits.
[0024] (2) In the process of preparing the medium-temperature curing epoxy resin glue of the present application, the quaternary ammonium salt compound and the amine compound respectively catalyze the ring-opening copolymerization reaction of the epoxy resin and the acid anhydride curing agent to form an ester and the self-polymerization reaction of the epoxy resin to form an ether. Then, by increasing the molar ratio of epoxy to acid anhydride, while the epoxy and acid anhydride copolymerize to form a polyester three-dimensional network structure, the epoxy resin self-polymerizes to form a polyether flexible chain, forming an interpenetrating or semi-interpenetrating cross-linked structure of polyester and polyether. This polyether flexible chain improves the alkaline corrosion resistance of the cured epoxy resin glue, improves the corrosion resistance to 5% sodium hydroxide by more than 5%, and improves the wear resistance by more than 3%. The resin casting is immersed in a 66°C medium for 30 days, and the flexural strength retention rate is ≥90%. After immersion for 6 months, the flexural strength retention rate of the resin matrix is ≥80%. In addition, the sanitary performance of the present application complies with the "Sanitary Safety Protection Specification for Drinking Water Transmission and Distribution Equipment and Protective Materials" (2001 edition).
[0025] (3) The fiber-reinforced plastic pressure-bearing pipe prepared in the present application can form a stable chemical bond between the fiber and the resin system interface during the winding process through the reasonable ratio of the various components of the epoxy resin adhesive, which is beneficial to enhancing the interfacial bonding force, improving the interfacial interlayer strength of the fiber-reinforced plastic and the rigidity of the separation membrane shell. It can also reduce the surface tension of the fiber in the high-viscosity resin, which is beneficial to the resin system passing through the internal gaps of the fiber bundle, so that the resin system and the fiber bundle form a tighter structure, improve the impact resistance of the product, and do not reduce the temperature resistance of the overall formula, improve the elongation at break of the matrix, enhance the toughness of the separation membrane shell, and reduce cracks, cracks or overhead caused by stress or external forces. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The infrared spectra of Example 1 and Comparative Example 1 are shown in FIG.
[0027] Figure 2 The DSC test curves of Example 3 and Comparative Example 3 at different heating rates. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0029] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0030] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.
[0031] The endpoints and any values of the ranges disclosed in the invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.
[0032] The following are the materials used in the examples:
[0033] Bisphenol A epoxy resin: epoxy value of epoxy resin is 0.48-0.54eq / 100g, viscosity is ≤11000-16000mPa·s (25℃), color is ≤2 (GB / T9281.1-2008), volatile matter is ≤1.5% (150℃, 40min).
[0034] Methyltetrahydrophthalic anhydride: acid value 660-685 mgKOH / g, anhydride content ≥40.5%, viscosity ≤60 mPa·s (25°C), color ≤300# (platinum-cobalt colorimetric), volatile matter ≤2% (150°C, 40min).
[0035] Dimethyldiallylammonium chloride: concentration is 65wt.% in H2O, color is colorless to light yellow transparent liquid, pH is 3-7.
[0036] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0037] Embodiment 1:
[0038] Take 100g of bisphenol A epoxy resin (E51) and 1g of triethanolamine, mix them, stir for 2min, and stir at a speed of 400r / min to obtain an epoxy resin mixture; take 65g of methyltetrahydrophthalic anhydride and 1.667g of dimethyldiallylammonium chloride, mix them, stir for 2min, and stir at a speed of 400r / min to obtain an anhydride mixture; pour the epoxy resin mixture into the anhydride mixture, stir for 2min, and stir at a speed of 400r / min. After vacuum degassing, cast it into a sample mold, cure it at 70°C for 2h, heat it to 120°C for curing for 3h, and naturally cool it to room temperature for use.
[0039] Embodiment 2:
[0040] Take 100g of bisphenol A epoxy resin (E51) and 1g of triethanolamine, mix them, stir for 2min, and stir at a speed of 400r / min to obtain an epoxy resin mixture; take 65g of methyltetrahydrophthalic anhydride and 1.667g of dimethyldiallylammonium chloride, mix them, stir for 2min, and stir at a speed of 400r / min to obtain an anhydride mixture; pour the epoxy resin mixture into the anhydride mixture, stir for 2min, and stir at a speed of 400r / min. After vacuum degassing, cast it into a sample mold, cure it at 70°C for 2h, heat it to 120°C for curing for 4h, and naturally cool it to room temperature for use.
[0041] Embodiment 3:
[0042] 100 g of bisphenol A epoxy resin (E51) and 1 g of triethanolamine were mixed, stirred for 2 min at a stirring speed of 400 r / min to obtain an epoxy resin mixture; 65 g of methyltetrahydrophthalic anhydride and 1.667 g of dimethyldiallylammonium chloride were mixed, stirred for 2 min at a stirring speed of 400 r / min to obtain an anhydride mixture; the epoxy resin mixture was poured into the anhydride mixture, stirred for 2 min at a stirring speed of 400 r / min, and the mixture was defoamed in vacuo for later use.
[0043] Comparative Example 1:
[0044] Take 100g of bisphenol A epoxy resin (E51), 75g of methyltetrahydrophthalic anhydride and 1g of N,N-dimethylbenzylamine, mix them, stir for 2min, and stir at a speed of 400r / min. After vacuum degassing, cast them in a sample mold, cure at 70℃ for 2h, heat to 120℃ for 3h, and cool naturally to room temperature for use.
[0045] Comparative Example 2:
[0046] Take 100g of bisphenol A epoxy resin (E51), 85g of methyltetrahydrophthalic anhydride, and 2g of N,N-dimethylbenzylamine, mix them, stir for 2min, and the stirring speed is 400r / min. After vacuum defoaming, cast them in a sample mold, cure at 90℃ for 2h, heat to 120℃ for 2h, heat to 160℃ for 2h, and cool naturally to room temperature for use.
[0047] Comparative Example 3:
[0048] Take 100 g of bisphenol A epoxy resin (E51), 75 g of methyltetrahydrophthalic anhydride, and 1 g of N,N-dimethylbenzylamine, mix them, stir for 2 min at a stirring speed of 400 r / min, and remove bubbles in vacuum for later use.
[0049] The tensile properties of Example 1 and Comparative Example 1 were tested according to GB / T 2567-2021 Test Method for Properties of Resin Castings to compare the differences in mechanical properties of different resin systems under the same curing system. The mechanical properties test results are shown in Table 1:
[0050] Table 1 Mechanical properties test results of Example 1 and Comparative Example 1
[0051]
[0052] As shown in Table 1, the tensile strength of the casting obtained by Example 1 is significantly higher than that of Comparative Example 1. Comparative Example 1 is a commonly used resin system in the industry, and it is also a resin system with mature technology and mechanical properties that meet industry requirements. The difference between the results of Example 1 and Comparative Example 1 is large because the resin of the method of the present invention can be completely cured at 120°C, while Comparative Example 1 needs to be completely cured at 160°C. Therefore, the maximum curing temperature is set to 120°C, and the degree of curing in Example 1 is higher. The higher the degree of curing, the more cross-linking points, the denser the network structure, and the high cross-linking density can significantly improve the mechanical properties of the resin; in addition, in resins with high curing degrees, the movement of molecular segments is restricted, which reduces the freedom and flexibility of the segments. This restriction enables the resin to better resist deformation when subjected to external forces, thereby increasing its elongation at break. According to the above test results, under the same curing system, the mechanical properties of the casting using the method of the present invention are better than those of Comparative Example 1.
[0053] Example 1 and Comparative Example 1 were tested by infrared spectroscopy. The results of the infrared spectroscopy test are as follows: Figure 1 As shown, in Example 1, the -1 The characteristic absorption peak of the epoxy group at 1250cm is more obvious than that in Comparative Example 1. This is because the ratio of epoxy resin to anhydride in Example 1 is larger, and there may be a small amount of unreacted epoxy resin residue. -1 The ether bond absorption peak at 1508 cm -1 The ester group absorption peaks at the positions are larger than those in Comparative Example 1, indicating that during the curing process, although there are residual epoxy resins in Example 1, the ring-opening copolymerization reaction of the epoxy resin and the acid anhydride curing agent catalyzed by the quaternary ammonium salt compound and the amine compound to form an ester and the self-polymerization reaction of the epoxy resin to form an ether are higher than those catalyzed by N, N-dimethylbenzylamine in Comparative Example 1, so that the degree of cross-linking of the casting is higher.
[0054] The castings of Example 2 and Comparative Example 2 were immersed in a 65°C, 5% sodium hydroxide solution for 30 days according to "GB / T 2567-2021 Test Method for Properties of Resin Castings", and the bending strength before and after alkali corrosion was tested respectively. The alkali resistance of Example 2 and Comparative Sample 2 was compared by strength retention rate. The results are shown in Table 2:
[0055] Table 2 Mechanical properties test results of Example 2 and Comparative Example 2
[0056] Sample Bending strength before alkali corrosion MPa Bending strength after alkali corrosion MPa Strength retention rate % Example 2 135 124 91.8 Comparative Example 2 137 116 84.7
[0057] As shown in Table 2, the bending strength retention rate of the casting of Example 2 after being immersed in 5% sodium hydroxide solution for one month is about 90%, while that of Comparative Example 2 is 85%. This is because a large number of ester bonds are formed in the process of forming the three-dimensional network structure of Comparative Example 2, and the ester bonds are easily hydrolyzed in alkaline solutions; while in Example 2, Catalyst 1 catalyzes part of the epoxy resin to self-polymerize to form a linear polyether structure, thereby reducing the curing reaction temperature of the epoxy self-polymerization reaction, thereby increasing the proportion of ether bonds in the three-dimensional network structure, showing a better resistance to alkali corrosion.
[0058] After vacuum degassing the mixtures of Example 3 and Comparative Example 3, DSC was scanned according to GB / T 19466.3-2004 "Plastics Differential Scanning Calorimetry (DSC) Part 3: Determination of Melting and Crystallization Temperatures and Thermal Enthalpy". The curing reaction temperatures of the two mixtures were measured at 5°C, 10°C, 15°C, and 20°C per minute. As the heating rate increased, the curing reaction temperature (peak value) continued to increase. Figure 2 As shown, at the same heating rate, the curing reaction temperature of Comparative Example 3 is higher than that of Example 3, and the curing reaction temperatures of Comparative Example 3 and Example 3 at different heating rates are fitted. According to the fitting curve, the curing reaction temperatures of Comparative Example 3 and Example 3 at 0°C / min are obtained, which are approximately 143°C and 123°C, respectively. According to the fitting data, the curing temperature of Example 3 is about 20°C lower than that of Comparative Example 3. Using Example 3 can reduce energy consumption, which can also explain that Example 3 can effectively reduce the reaction starting temperature compared with Comparative Example 3.
[0059] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a medium temperature curing epoxy resin glue, characterized in that: The method: S1: adding a wetting agent and an amine compound to a bisphenol A epoxy resin, stirring uniformly, and obtaining a mixture; S2: adding a toughening agent and a quaternary ammonium salt compound to the acid anhydride, stirring evenly to obtain a mixture; S3: Pour the S1 mixture into the S2 mixture and stir evenly; S4: adding an anti-aging agent, stirring evenly, adding a thickener, stirring evenly, and obtaining epoxy resin glue after defoaming treatment.
2. The method according to claim 1, characterized in that The mass ratio of bisphenol A epoxy resin, acid anhydride, quaternary ammonium salt compound and amine compound is 90-110:60-80:1-3.5:0.3-2, the wetting agent is 0-3% of the mass of the epoxy resin, the toughening agent is 0-10% of the mass of the epoxy resin, the anti-aging agent is 0-2% of the mass of the epoxy resin, and the thickener is 0-5% of the mass of the epoxy resin.
3. The method according to claim 1, characterized in that The acid anhydride is methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride or endomethylenetetrahydrophthalic anhydride, the wetting agent is alkyl glycidyl ether polymer or N-(hydroxyalkyl)amine condensation polymer, the toughening agent is polypropylene glycol diglycidyl ether, fatty acid polyglycidyl ether, carboxyl liquid nitrile rubber or polyvinyl butyral, the antioxidant is a benzotriazole mixture, phenylformamidine compound, fluoroboryl acrylate or phenoxy mercuric alcohol, the thickener is white carbon black, the quaternary ammonium salt compound is DADMAC, DAC, DMC or MAPTAC, and the amine compound is triethanolamine, tris(2-hydroxypropyl)amine, tris(2-hydroxyethyl)methylamine or tris(2-hydroxyethyl)aminopropylamine.
4. The method according to claim 1, characterized in that In S1, S2, S3 and S4, the stirring time is 2-5 min, and the stirring speed is 50-500 r / min.
5. A medium temperature curing epoxy resin glue, characterized in that: Prepared by the method according to any one of claims 1 to 4.
6. Use of the medium-temperature curing epoxy resin adhesive according to claim 5 in fiber-reinforced plastic pressure-bearing pipes.
7. A fiber reinforced plastic pressure pipe, characterized in that: The fiber reinforced plastic pressure-bearing pipe is prepared from the epoxy resin glue and fiber filaments described in claim 5.
8. The method for preparing a fiber reinforced plastic pressure pipe according to claim 7, characterized in that: The method: The fiber filaments are immersed in the epoxy resin glue described in claim 5, and then processed and prepared by a pipe mold thermosetting process.
9. The method according to claim 8, characterized in that The curing time of the thermosetting process is divided into two stages. The first stage is at a temperature of 70-80°C and a constant temperature time of 2-3 hours. The second stage is at a temperature of 110-130°C and a constant temperature time of 4-6 hours.
10. Use of the fiber reinforced plastic pressure pipe according to claim 7 in drainage.
Citation Information
Patent Citations
High-performance epoxy resin composition for sheet molding compound (SMC)
CN102337007A
Curing agent special for pultrusion, and application thereof
CN106432691A
Waterproof quaternary ammonium salt / epoxy thermosetting material and preparation method thereof
CN114479355A
Method for catalyzing copolymerization of anhydride and epoxy by using fluorine catalyst
CN115536825A
Preparation method of epoxy resin chlorine content standard substance
CN116794203A
Cited By
Antibacterial resin system and manufacturing method of antibacterial inner surface of separation membrane
CN120699392A